Novel Materials for 3D Printing by Photopolymerization - Layani, Michael; Wang, Xiaofeng; Magdassi, Shlomo (Advanced materials (Weinheim), 2018)
The field of 3D printing, also known as additive manufacturing (AM), is developing rapidly in both academic and industrial research environments. New materials and printing technologies, which enable rapid and multimaterial printing, have given rise to new applications and utilizations. However, the main bottleneck for achieving many more applications is the lack of materials with new physical properties. Here, some of the recent reports on novel materials in this field, such as ceramics, glass, shape‐memory polymers, and electronics, are reviewed. Although new materials have been reported for all three main printing approaches—fused deposition modeling, binder jetting or laser sintering/melting, and photopolymerization‐based approaches, apparently, most of the novel physicochemical properties are associated with materials printed by photopolymerization approaches. Furthermore, the high resolution that can be achieved using this type of 3D printing, together with the new properties, has resulted in new implementations such as microfluidic, biomedical devices, and soft robotics. Therefore, the focus here is on photopolymerization‐based additive manufacturing including the recent development of new methods, novel monomers, and photoinitiators, which result in previously inaccessible applications such as complex ceramic structures, embedded electronics, and responsive 3D objects. Photopolymerization‐based 3D printing materials have been reported widely in recent years. Various materials such as hydrogels, ceramics, and responsive polymers, along with new applications of these materials and methods are described.